Efektivitas pengolahan limbah cair hotel dan implementasi keputusan Menteri Lingkungan Hidup nomor 52/menlh/10/1995 tentang baku mutu limbah cair bagi kegiatan hotel di Kota Pekanbaru - Syafri Boy; Aras Mulyadi; Sukendi Sukendi (Pelantar Press, 2017)
This research aims to determine the effectiveness of the treatment of waste water hotel and see Implemantation Decree of the Minister of Environment No.52/MENLH/10/1995 concerning the Waste water Quality Hotel by five-star hotel in the city of Pekanbaru. The method used in this research is the survey and interview. Based on the analysis we found that the rate of decrease in the content of pollutants in the waste water hotel in reducing the content of pollutants in the waste water for parameters BOD, COD, TSS and pH respectively 72%, 75%, 25% and 16%. IPL Cability levels in the lower levels of waste water sample parameters for the parameters BOD, COD, TSS and pH respectively 60.0%, 30.0%, 50.0% and 87.5%. IPLC analysis results in Pekanbaru compared with the Waste water Quality Standard Hotel, pollutant levels are still above the environmental quality standards.